Gegar Budaya pada Mahasiswa Perantauan terhadap Lingkungan Sekitar - Dewi, Melyana Putricia; Setyanto, Yugih (Kiwari, 2025)
Culture shock is a psychological phenomenon that a person experiences when they are in a cultural environment that is different from their place of origin. Various symptoms such as confusion, anxiety, and feelings of alienation are the result of differences in values, norms, and social interaction patterns that are not the same as those usually encountered in their place of origin. This research was conducted to analyze the factors that cause culture shock and the strategies used by new students at Tarumanagara University. The theories used in this research are communication theory, culture shock theory, intercultural communication theory, cultural theory, adaptation theory, student theory, and migration theory. The research method used is a qualitative research method with a phenomenological approach with primary and secondary data sources in the form of interviews, observation and documentation. Interviews were conducted with migrant students at the Tarumanagara University Campus. The results of this research show that the cultural shock experienced by the interviewees took various forms, such as language differences, different patterns of communication or interaction styles and the role of peers in the adaptation process. This research concludes that social support, either from fellow students or organizations, plays an important role in helping the adaptation process. Gegar budaya adalah fenomena psikologis yang dialami seseorang ketika berada di lingkungan budaya yang berbeda dari tempat asalnya. Berbagai gejala seperti kebingungan, kecemasan, dan perasaan terasing adalah hasil dari perbedaan nilai, norma, dan pola interaksi sosial yang tidak sama dengan yang biasa dihadapi di tempat asal. Penelitian ini dilakukan untuk menganalisis faktor-faktor yang menyebabkan terjadinya gegar budaya dan strategi yang digunakan pada mahasiswa baru Universitas Tarumanagara. Teori yang digunakan dalam penelitian ini adalah teori komunikasi, teori culture shock, teori komunikasi antar budaya, teori budaya, teori adaptasi, teori mahasiswa, dan teori perantauan. Metode penelitian yang digunakan adalah metode penelitian kualitatif dengan pendekatan fenomenologi dengan sumber data primer dan sekunder berupa wawancara, observasi dan dokumentasi. Wawancara dilakukan dengan mahasiswa perantau yang berada di Kampus Universitas Tarumanagara. Hasil penelitian ini menunjukkan bahwa gegar budaya yang dialami narasumber dalam berbagai bentuk, seperti perbedaan bahasa, pola gaya komunikasi atau berinteraksi yang berbeda dan peran teman sebaya dalam proses beradaptasi. Penenlitian ini menyimpulkan bahwa dukungan sosial, baik dari sesama mahasiswa atau organisasi merupakan peran yang penting dalam membantu proses adaptasi.